Finite Element Analysis of Seepage and Exit Gradient through a Homogeneous Earth Dam without Cut-Off Walls by using Geo-Slope (SEEP/W) Software - Arshad, Imran; Babar, Muhammed Muneer (PSM Biological Research, 2020)
In this study, a homogeneous section of an earthen dam (Hub dam) with and without cut-off wall was analyzed by using FEM based software SEEP/W. The FEM model was run to compute the behavior of the dam in terms of seepage flux and exit gradient for three different scenarios i.e. maximum (346 ft), minimum (270 ft), and normal pool level (339 ft) respectively. The simulated results for case (i) with cut-off wall showed that the dam is safe against piping, at its original design with overall minimum seepage flux of (2.513 x 10-4 ft3/sec/ft) and exit gradient (0.351) at downstream toe respectively. However, for case (ii) without cut-off wall, the dam showed abnormal behavior as an overall extremely high exit gradient (1.879) along with the maximum overall seepage flux of order 17.182 x 10-4 ft3/sec/ft respectively. The comparison showed that seepage flux (29.382% – 76.946%) and exit gradient (68.604% – 75.845%) through the dam and its foundation was found more when there are no cut-off walls. Which is the result of continuous movement of the water within the dam especially in the foundation, as there is no any barrier installed to control internal pore water pressure, due to which the water seeping from the upstream and foundation finds its way moving towards the downstream and cuts the toe to make its way out respectively.